2014
DOI: 10.1513/annalsats.201312-423oc
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency at 16 to 20 Weeks’ Gestation Is Associated with Impaired Lung Function and Asthma at 6 Years of Age

Abstract: This study supports the notion that vitamin D deficiency during lung development may impact on postnatal lung growth and increase the risk of developing lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 38 publications
7
114
2
6
Order By: Relevance
“…In keeping with the animal data, a recent human study (109) showed that lower maternal vitamin D concentrations in pregnancy were after confounder control associated with current wheeze (both sexes, questionnaire data, P ϭ 0.05), current asthma (boys, doctor's diagnosis, P ϭ 0.04), decreased functional vital capacity (FVC) Z-score (both sexes, P ϭ 0.02, largely driven by decreased FVC in girls), a trend toward lower forced expiratory volume in 1 s (FEV1) Z-score at 6 yr (girls, P ϭ 0.09), and decreased FEV1/FVC Z-score in 14-yr-old girls (P ϭ 0.05). Whereas some other studies support an inverse relation between vitamin D status in pregnancy and offspring wheeze or asthma, others have found no associations, or U-shaped or direct associations, although many of these studies were of minor quality, e.g., in the diagnosis of childhood asthma (62,63).…”
Section: Discussionmentioning
confidence: 92%
“…In keeping with the animal data, a recent human study (109) showed that lower maternal vitamin D concentrations in pregnancy were after confounder control associated with current wheeze (both sexes, questionnaire data, P ϭ 0.05), current asthma (boys, doctor's diagnosis, P ϭ 0.04), decreased functional vital capacity (FVC) Z-score (both sexes, P ϭ 0.02, largely driven by decreased FVC in girls), a trend toward lower forced expiratory volume in 1 s (FEV1) Z-score at 6 yr (girls, P ϭ 0.09), and decreased FEV1/FVC Z-score in 14-yr-old girls (P ϭ 0.05). Whereas some other studies support an inverse relation between vitamin D status in pregnancy and offspring wheeze or asthma, others have found no associations, or U-shaped or direct associations, although many of these studies were of minor quality, e.g., in the diagnosis of childhood asthma (62,63).…”
Section: Discussionmentioning
confidence: 92%
“…Dysanapsis is merely a reflection of the incongruence between a (faster) growth in lung volume and airway length, and the (slower) increase in airway caliber. Such incongruence may happen physiologically and may be accentuated by several mechanisms, including in utero exposures such as tobacco smoke or vitamin D deficiency (34,35), although it is unclear whether these effects would persist later in childhood. Chronic hypoxemia has been associated with a higher risk of dysanaptic lung growth (36); dysanapsis may also be present in breathhold divers, who use glossopharyngeal insufflation to force their lung volumes above TLC (providing extra oxygen and preventing compression when diving) (37).…”
Section: Discussionmentioning
confidence: 99%
“…33,47,48 The 9 studies with nonsignificant results used a variety of 25(OH)D thresholds. 29,30,32,[40][41][42][43][44]46 None of the 6 studies looking at the association between 25(OH)D and allergic rhinitis reported significant associations. 29,30,41,43,44,48 One study mentioned collecting data but did not report on the outcome.…”
Section: Allergic Diseasementioning
confidence: 99%